The relationship between total quality management practices and organisational image in the hospital industry: an empirical examination. (10th January 2020) - Babu, Faisal; Thomas, Sam
The purpose of this paper is to depict the role of leadership in implementing total quality management (TQM) practices in hospitals and their relationship to the formation of the organisational image by investigating the perceptions of hospital leaders in the context of the Indian healthcare system. A survey of 265 employees including administrators, managers and heads of departments of 15 NABH-accredited hospitals in Kerala was conducted based on a questionnaire. Structural equation modelling (SEM) was done with the use of WarpPLS 50 to test the structural model. The study revealed that leadership is acting as the key driver in implementing quality systems in hospitals. Further, management leadership and the other four TQM practices - information and analysis, human resource management, process management and supplier management - were the significant predictors of the organisational image.